Formation of linguocultural competence of language specialties’ students on the example of proverbs with zoonyms - Ashimkhanova, S.Z.; Bekturganova, A.O.; Omarova, A.O. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The article deals with the formation of linguocultural competence of language specialties’ students on the example of proverbs with zoonyms. Modern studies on methods of teaching English language is focused on the relation between language, history and culture. The acknowledgement of the importance of the cultural component in research is closely connected with the usage of cognitive approach. Taking into consideration linguocultural aspect of teaching foreign languages authors offer set of tasks which help to develop linguocultural competence of the students.
Тілдік мамандықтар студенттерінің лингвомəдени құзыреттілігін зоонимдері бар мақал-мəтелдер негізінде қалыптастыру
Формирование лингвокультурологической компетенции студентов языковых специальностей на примере изучения пословиц с зоонимами
Keywords: linguocultural competence; zoonyms; proverbs; language specialties’ students; culture; animal images; symbol; history; customs